Liquidity constraints and demand for maturity the case of mortgages - Alessandro Ferrari; Marco Loseto (European Central Bank (ECB), 2023)
Using administrative data on mortgages issued in Italy between 2018 and 2019, this paper estimates loan demand elasticities to maturity and interest rate. We find that households are responsive to both contract terms: a 1% decrease in interest rate increases the average loan size by 0.22% whereas a commensurable increase in maturity increases loan demand by 0.30%. This evidence suggests that credit constraints are relevant in this market. Things change substantially when moving along the distribution of contract maturities: short term borrowers are unresponsive to their contract length while maturity elasticities are higher for long term borrowers.
Keywords: D12; D14; D15; G11; G51; 330; mortgage; household finance; credit demand; maturity